2019
DOI: 10.4081/or.2019.7866
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion rate, hospital stay and cost-effectiveness of intravenous or local administration of tranexamic acid in total hip and knee arthroplasty: A single-center randomized controlled clinical study

Abstract: We have conducted a prospective randomized study to determine the effect of intravenous or local administration of tranexamic acid (TXA) in perioperative transfusion rates, hospital stay and overall hospitalization costs in patients underwent total knee (TKA) or total hip (THA) arthroplasty. During 2015- 2016, 125 THA and 124 TKA consecutive patients were randomly allocated to receive low dose TXA either intravenously (ivTXA groups) or local administration (locTXA groups) or to serve as controls. Power analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 22 publications
1
14
0
4
Order By: Relevance
“…The difference between preoperative and postoperative haemoglobin levels could be used as an indication of perioperative blood loss [21]. The results are comparable with other studies which report a postoperative haemoglobin drop of between 21 % to 28.5 % [21,22]. The postoperative haemoglobin check, however, was performed in these trials on the third postoperative day and not, as in the present work, on the second postoperative day.…”
Section: Complicationsupporting
confidence: 86%
See 1 more Smart Citation
“…The difference between preoperative and postoperative haemoglobin levels could be used as an indication of perioperative blood loss [21]. The results are comparable with other studies which report a postoperative haemoglobin drop of between 21 % to 28.5 % [21,22]. The postoperative haemoglobin check, however, was performed in these trials on the third postoperative day and not, as in the present work, on the second postoperative day.…”
Section: Complicationsupporting
confidence: 86%
“…Transfusion rates after total prosthetic hip replacement generally demonstrate large ranges of variation of between 4 % to 68 % [23]. Studies without the perioperative administration of tranexamic acid report transfusion rates of between 37 % to 62.8 % [21,22]. Accordingly, the postoperative blood transfusion rate in all three groups is generally low and demonstrates a significantly lower rate under certified standards.…”
Section: Complicationmentioning
confidence: 99%
“…TXA has been proven to reduce perioperative blood loss and transfusion cost in various surgical procedures. [ 18 , 19 ] However, few study has reported the use of TXA in long-segment spinal fusion surgery. Thus, no consensus has been reached on the optimal regimen of the TXA delivery.…”
Section: Discussionmentioning
confidence: 99%
“…23 Therefore reducing cost as well as hospital stay. 25,26 Despite the higher risk of blood loss and need for transfusion following revision total knee arthroplasty, lowest effective dose and least costly regimen should be used due to similar effect in the management of blood loss with all TXA dosing regimens. 27 Efficacy of TXA in gynecology and obstetrics i).…”
Section: Efficacy In Knee and Hip Arthroplastymentioning
confidence: 99%